Oral Medicine and Pharmacology Teleconsulting Sessions of the Telehealth Program in one Southeastern State of Brazil - Lígia Cristelli Paixão; Vanessa Andrade Costa; Gustavo Pina Godoy; Efigênia Ferreira Ferreira; Antônio Paulino Ribeiro-Sobrinho; Renata Castro Martins (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate questions concerning oral medicine- and pharmacology-related specialties of asynchronous dental teleconsulting sessions of the Telehealth Brazil Networks Program. Material and Methods: Data were collected from secondary databases of asynchronous dental teleconsulting sessions of the telehealth centers of Minas Gerais from July 2015 to July 2017. The variables for dental underlying fields and the types of questions were evaluated. Descriptive analysis was performed with the SPSS v.22.0 program. Results: 3,920 teleconsulting sessions were referred to the telehealth centers of Minas Gerais during the study period. Regarding oral medicine-related questions (n=745), most (n=469; 62.95%) addressed diagnosis, whereas the underlying field questions mostly regarded fungal, viral, and bacterial infections (17.3%), biopsies (16.4%), developmental defects and dental abnormalities (9.9%), and soft tissue tumors (9.4%). Pharmacology-related questions (n=738) mostly addressed general approaches (n=672; 91.06%), and the most common questions were about underlying fields' prescriptions (44.7%), anesthetics (17.6%), adverse effects of medications and anesthetics (10.2%), and selection of anesthetics for patients with systemic conditions (9.8%). Conclusion: Most teleconsulting sessions regarded conditions or procedures common in primary health care and essential for diagnosis and treatment planning at all care levels, which suggests a need for more academic learning processes for healthcare professionals, especially in dentistry primary fields.